Analysis of packet loss rate based on the measured traffic - Ting MI; Wei DING (Tongxin xuebao)
The packet loss rate is one of key indicators to evaluate the performance of network.A method for calculating packet loss rate in the measured data based on the intact TCP flows was presented.Based on the measured data,the packet loss rate of Jiangsu Province in CERNET network and different partitions outside was analysed.The algorithm gives the packet loss rate including first packet loss rate pfl,overall packet loss rate psland retransmission rate prp.Through statistical analysis,pflis smaller than pslin the vast majority of cases,and prpis significantly higher than pfland psl,which proves the impact of packet loss on the performance of network,and retransmission rate is obviously higher than packet loss rate.